Global climates since the last glacial maximum - Wright, H. E., Jr. (Herbert Edgar), 1917-2015 (University of Minnesota Press, 1993)
Summarizes much of the geologic, paleoecologic, and oceanographic evidence for global environmental and climactic changes during the last 18,000 years.